Capturing the Face of the Music Industry's Business Strategy - I Made Rai Nurcahya Widhiantara Suyasa; Agus Fredy Maradona (GoAcademica Research & Publishing, 2023)
This research aims to Photograph the Face of Music Industry Business strategy by identifying external and internal factors that affect the music industry business model in Bali. And to find out the use of the Business Model Canvas (BMC) approach in the music industry in Bali. The method used in this research is descriptive-qualitative. The data collection used interviews and documentation. The results of the analysis show that the strengths of the music industry in running the business are quality equipment, a wide range of customers, and a diverse customer base. The weaknesses owned by the music industry in Bali are the rapid pace of audio technology, meaning that more and more people can make their own recordings with easily accessible applications. Related to the threats faced by the music industry in Bali are Affordable recording equipment and ease of use. In the development of the canvas business model from the value proposition point of view, the music industry in Bali can use remote services and advanced technology. This is done by the manager of the music industry in Bali so that it continues to exist to get through times of crisis such as the COVID pandemic.